Traversing Transnational Biomedical Landscapes: An Ethnography of the Experiences of Nigerian Trained Physicians Practicing in the US and UK - Schühle, Judith (transcript, 2020)
In the age of globalization, the transnational dimension of sciences like medicine seems to be given. However, the agents connecting different parts of this transnational biomedical landscape have yet to receive their due attention. Situated at the intersection of contemporary debates as well as theories of medical anthropology and migration in the 21st century, this book explores the experiences of Nigerian trained physicians who migrated to the US and the UK within the last 40 years. By drawing on individual professional life stories, Judith Schühle illuminates how these physicians disconnect from and (re)connect to diverse local social and biomedical contexts, becoming established abroad while at the same time trying to influence health care services in Nigeria through transnational endeavors.